THE IMPORTANCE OF PREVENTIVE PHYSIOTHERAPY FOR THE HEALTH OF THE ELDERLY (REMUNOM, 2023)
This academic article aims to address the importance of preventive physiotherapy for the health of the elderly, since according to data on the demographic transition in Brazil, the population is increasingly older. With this, it is necessary that the State, society and health professionals know how to deal with the aging process and its consequences. For that, a bibliographical research was carried out in books, websites and academic articles that deal with the subject. In the end, it was observed that preventive physiotherapy is extremely important in caring for the elderly, as it is focused on the health of the elderly as a whole, working their entire body in general, that is, the cardiac, muscular, respiratory, motor and balance.